Peran gaya kepemimpinan servant leadership terhadap peningkatan partisipasi akademik mahasiswa dan dosen prodi piaud di Perguruan Tinggi - Ulfah Hidayati (STAI Syekh Jangkung, 2024)
This study aims to provide an in-depth description of the role of servant leadership in enhancing the academic participation of students and lecturers in the Early Childhood Islamic Education (PIAUD) Study Program at STAI Syekh Jangkung. This leadership style emphasizes service, empathy, and the empowerment of organizational members, thereby fostering a collaborative, inclusive, and productive academic climate. The research employed a qualitative descriptive method, with data collected through interviews, observations, and documentation. The results indicate that the implementation of servant leadership by the program head has positively contributed to increasing lecturers’ participation in research and community service activities, as well as encouraging students to be more active in scientific events, class discussions, and student organizations. These findings affirm that service-oriented leadership can serve as an effective leadership model in Islamic higher education institutions.